Enhancing Listening Comprehension through Frozen 2 Movie - Ginarti Eka Hamidah; Muhamad Sofian Hadi (Universitas Pendidikan Mandalika, 2021)
As an international language, English has become one of the most commonly spoken languages globally, and mastering the English language is necessary for us. This research aimed to answer the research question, namely Enhancing Listening Comprehension Through Frozen 2 Movie. The researcher wants to know whether using the Frozen 2 movie will help students in increasing their listening comprehension or not. This research using a case study of pre-experimental as the research design. The study involved 16 participants of Senior High School around Griya Serpong Asri, Tangerang. The data was derived from pre-test and post-test. The researcher collected it during the research time. The outcome appeared that there is a massive impact on establishing listening comprehension by watching frozen 2 movies as media in the learning process. With the result 0.003 < α (0.05), which means H1 was accepted and H0 was rejected. This research shows several advantages of using Frozen 2 movies as media in the learning process, such as frozen 2 movies as interesting media. Students don’t get bored easily by watching the movie. Also, students can learn body language, facial expressions while listening to the native speaker in the movie.